The present and future of withdrawal period calculations for milk in the European Union: dealing with data below the limit of quantification. Issue 2 (31st July 2016) - Henri, J.; Jacques, A.‐M.; Sanders, P.; Chevance, A.; Laurentie, M.
Abstract : The assessment of withdrawal periods for milk is affected by the occurrence of data below the lower analytical quantification limit (BLQ data) and the resulting uncertainty. The current regulatory approach for dealing with BLQ residues is simple and easy: BLQ data (and missing data) are arbitrarily reassigned a value of one‐half the LOQ before any calculation on the data with one of the three currently applicable methods. Here, we reconsider the determination of the withdrawal period of milk with data below the limit of quantification. Theoretical background on analytical limits and pharmacometric considerations will be established. Then, we analyze the uncertainty problems caused by the current approach and propose a calculation solution (maximum‐likelihood estimation handling left‐censored data) included in nonlinear mixed‐effects modeling. Finally, we illustrate this issue using a case example.